PENGEMBANGAN PROFESIONALISME GURU MELALUI MANAJEMEN KEPEMIMPINAN KEPALA SEKOLAH - Sakiman (CV. Amerta Media, 2020)
Leadership is important to be of particular concern, this is because through leadership quality teachers and employees will be born. In the school the main leader is the principal. The principal is responsible for the purpose of the school, which is to provide active and fun education. The results showed that the principal's leadership in developing teacher professionalism through four main functions, namely: planning, organizing, actuating and controlling. The principal's efforts in developing teacher professionalism are by directing teachers to read and write scientifically, especially about education. In addition, teachers must also attend training, KKG and participate in professional organizations. Through these efforts, teacher professionalism will develop.Key Word: leadership, principals, teachers.